Thermal conductivity of ultrathin BaTiO3 films grown by plasma-assisted atomic layer deposition. (September 2018) - Cho, Jungwan; Park, Joonsuk; Prinz, Fritz B.; An, Jihwan
Abstract: We report the first measurements of the room temperature thermal conductivity of ultrathin (12 and 24 nm) barium titanate (BaTiO3 ) films prepared by plasma-enhanced atomic layer deposition (PEALD). The measured thermal conductivities of as-deposited films are relatively low as compared to values reported previously. We further investigate the effects of a post-deposition remote oxygen plasma treatment on the crystallinity and thermal conductivity of our PEALD BaTiO3 films. We find that the thermal conductivity slightly decreases with increasing duration of plasma treatment, which is most likely due to increased phonon scattering at interfaces between amorphous and crystalline phases within the films. Graphical abstract: Unlabelled Image